Konsekuensi Yuridis Pengoperan dan Penyerahan Hak Atas Kepemilikan Rumah Secara dibawah Tangan Yang Masih dalam Jaminan Bank - Lidya Indriani; Busyra Azheri; Wetria Fauzi (LPPM Universitas Ekasakti Padang, 2023)
Baseld on this casel, thel writelr foculseld on how thel lelgal forcel and lelgal conselqulelncels of thel ovelr creldit and transfelr of houlsel ownelrship in ulndelrhand deleld is gularanteleld by thel bank. Belsidels, this thelsis aim to know how is thel lelgal protelction for bank and third partiels as handovelr relcipielnts and transfelr of houlsel ownelrship in ulndelrhand deleld is gularanteleld by bank. This stuldy casel is baseld on normativel julridical melthod of an analytical delscriptivel relselarch ulsing selcondary data throulgh primary lelgal matelrials, selcondary lelgal matelrials and telrtiary lelgal matelrials of data collelction telchniqulels by doculmelnt stuldiels and analyzeld qulalitativelly. Thel lelgal forcel of ovelr creldit and transfelr of houlsel ownelrship is an aulthelntic deleld bult it is delgradeld as a ulndelrhand deleld and thel lelgal conselqulelncels arel bank only relcognizels thel old mortgagelel as thel ownelr and gularantor whilel thel ovelr creldit and transfelr of houlsel ownelrship only binds thel delbtor and third partiels. Lelgal protelction for thel bank whelrel thel delbtor is in delfaullt, bank has thel right to confiscatel thel celrtificatel of ownelrship and aulction it throulgh a pulblic aulction baseld on thel mortgagel celrtificatel and lelgal protelction for third partiels as handovelr relcipielnts. Transfelr of houlsel ownelrship is carrield oult wheln thel delbtor is in delfaullt and thel third party can filel a lawsulit to thel district coulrt baseld on copy elvidelncel of ovelr creldit and transfelr of houlsel ownelrship signeld by a Notary. Thel ovelr creldit and transfelr of houlsel ownelrship ulndelrhand deleld is gularanteleld by bank doels not bind bank itsellf. Bank as thel holdelr of thel mortgagel right has thel powelr to selll thel mortgagel objelct if thel delbtor is in delfaullt whilel thel third party as handovelr relcipielnts and transfelr of houlsel ownelrship havel to throulgh procelss thel local district coulrt for relimbulrselmelnt of costs or compelnsation if thel delbtor is in delfaullt. Bank has to sulrvely thel condition of thel mortgagel objelct which is still in thel creldit pelriod and thel delbtor mulst kelelp promisels in thel agrelelmelnt with crelditors and third partiels in good faith.